2011
DOI: 10.3168/jds.2010-3715
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: Effect of udder health management practices on herd somatic cell count

Abstract: A systematic review of the scientific literature on relationships between management practices used on dairy farms and herd somatic cell count (SCC) was undertaken to distinguish those management practices that have been consistently shown to be associated with herd SCC from those lacking evidence of association. Relevant literature was identified using a combination of database searches (PubMed, Medline, CAB, Agricola, and Web of Science) and iterative screening of references. To be included in the review, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
125
2
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(141 citation statements)
references
References 47 publications
7
125
2
7
Order By: Relevance
“…Chi-square relationship tests supported the above results so that herds with manual cluster removal systems showed the highest frequency of cows with SCC ]150 000 (Table 1). The results obtained in the study are in agreement with those in most of the literature as reviewed by Dufour et al (2011), where it was found that automatic cluster removal systems are associated with lower SCC when deployed correctly. In 28% of investigated farms, clusters were removed manually.…”
Section: Resultssupporting
confidence: 82%
“…Chi-square relationship tests supported the above results so that herds with manual cluster removal systems showed the highest frequency of cows with SCC ]150 000 (Table 1). The results obtained in the study are in agreement with those in most of the literature as reviewed by Dufour et al (2011), where it was found that automatic cluster removal systems are associated with lower SCC when deployed correctly. In 28% of investigated farms, clusters were removed manually.…”
Section: Resultssupporting
confidence: 82%
“…Diseases such as foot-rot which cause significant pain in ruminants, should be targeted for eradication, as has been done in some countries (e.g., Norway [127] and Australia [128]); this is a very effective way of preventing pain and suffering. Incidence of mastitis can be prevented through good housing and hygiene management in the milking parlor as well as in bedded areas [129][130][131]. Disease prevention also comes from early treatment of the disease so as to prevent the spread of infection, reducing the number of animals affected, but also reducing the amount of time animals with the disease will experience pain.…”
Section: Preventing Pain From Occurringmentioning
confidence: 99%
“…Tools for SCC measurement, such as the California Mastitis Test, may have limited sensitivity and specificity, but their low cost, speed, ease of use, and quarter level results make them valuable in a herd screening and sampling program. Frequent use of the California Mastitis Test has in literature been consistently associated with low HSCC (Dufour et al 2011). Quarter level information on infection status can be important for treatment or culling decisions ) (see further).…”
Section: Bacteriological Culturementioning
confidence: 99%
“…Try to determine when the milking machine was last serviced and how frequently this is done. Milking practices that have consistently been associated with low SCC herds are wearing gloves during milking, using automatic take-offs, using post-milking teat dipping, milking problem cows last, yearly inspection of the milking system, and use of a technique to keep cows standing following milking (Dufour et al 2011). If infected cows, in particular those with S. aureus, cannot be milked last, each teat cup should be manually disinfected by flushing it with hot water (>75 C) for several seconds or by immersing the unit into a hypochlorite, iodine, or peracetic acid solution after milking an infected cow.…”
Section: Milkingmentioning
confidence: 99%